2021
DOI: 10.1097/aln.0000000000003736
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Respiratory Muscle Thickness during Mechanical Ventilation: Focus on Expiratory Muscles

Abstract: Background The lateral abdominal wall muscles are recruited with active expiration, as may occur with high breathing effort, inspiratory muscle weakness, or pulmonary hyperinflation. The effects of critical illness and mechanical ventilation on these muscles are unknown. This study aimed to assess the reproducibility of expiratory muscle (i.e., lateral abdominal wall muscles and rectus abdominis muscle) ultrasound and the impact of tidal volume on expiratory muscle thickness, to evaluate chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 44 publications
0
42
0
1
Order By: Relevance
“…Importantly, these alternations do not exclusively affect the diaphragm but, although less rapid, may also affect the other Abbreviations: IMT, inspiratory muscle training; PImax, maximal inspiratory pressure; PoB, power of breathing; %StiO 2 , muscle oxygen saturation index; ICU, intensive care unit; EMG, electromyographic; NIRS, near-infrared spectroscopy; COPD, chronic obstructive pulmonary disease; APACHE II, Acute Physiology and Chronic Health Evaluation II Scale; WoB, work of breathing; FVC, forced vital capacity; PIF, peak inspiratory flow; Hb, hemoglobin; Mb, myoglobin; MAP, mean arterial blood pressure. inspiratory and expiratory muscles (Bernard et al, 2003;Capdevila et al, 2003;Shi et al, 2021). Specifically, studies in animal models have found that after 48 h on mechanical ventilation external intercostal muscle of rabbits demonstrated contractile dysfunction and reduction in cross-sectional area of type II fibers (Bernard et al, 2003;Capdevila et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, these alternations do not exclusively affect the diaphragm but, although less rapid, may also affect the other Abbreviations: IMT, inspiratory muscle training; PImax, maximal inspiratory pressure; PoB, power of breathing; %StiO 2 , muscle oxygen saturation index; ICU, intensive care unit; EMG, electromyographic; NIRS, near-infrared spectroscopy; COPD, chronic obstructive pulmonary disease; APACHE II, Acute Physiology and Chronic Health Evaluation II Scale; WoB, work of breathing; FVC, forced vital capacity; PIF, peak inspiratory flow; Hb, hemoglobin; Mb, myoglobin; MAP, mean arterial blood pressure. inspiratory and expiratory muscles (Bernard et al, 2003;Capdevila et al, 2003;Shi et al, 2021). Specifically, studies in animal models have found that after 48 h on mechanical ventilation external intercostal muscle of rabbits demonstrated contractile dysfunction and reduction in cross-sectional area of type II fibers (Bernard et al, 2003;Capdevila et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Diaphragm biopsies of mechanically ventilated patients have demonstrated increased proteolysis and decreased protein synthesis, enhanced number of inflammatory cells and loss of muscle mass as important underlying mechanisms to explain reduced force output of the diaphragm ( Vassilakopoulos and Petrof, 2004 ; Hooijman et al, 2015 ; Berger et al, 2016 ). Importantly, these alternations do not exclusively affect the diaphragm but, although less rapid, may also affect the other inspiratory and expiratory muscles ( Bernard et al, 2003 ; Capdevila et al, 2003 ; Shi et al, 2021 ). Specifically, studies in animal models have found that after 48 h on mechanical ventilation external intercostal muscle of rabbits demonstrated contractile dysfunction and reduction in cross-sectional area of type II fibers ( Bernard et al, 2003 ; Capdevila et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 In a study of 77 adult patients requiring MV and evaluated with POCUS, 17 (22%) had a decrease of > 15% in expiratory muscle thickness during the first week of MV. 16 In a study of 35 pediatric patients requiring MV, 15 (44%) had a decrease of > 10% in expiratory thickness over the first 4 days of MV. In the latter study, the decrease in expiratory muscle thickness was significantly higher in patients failing extubation compared to those with successful extubation, suggesting that decreases in expiratory muscle thickness may be an early predictor of weaning failure.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] In addition to the adverse effects on the diaphragm attributed to VIDD (longer weaning times, ventilation time and weaning failure), recent investigations of POCUS evaluating the expiratory muscles of the lateral abdominal wall have found similar adverse effects of mechanical ventilation (MV) on these important respiratory muscles resulting in weaning difficulty as well as impaired airway clearance. [16][17][18] Children with medical complexity (CMC) have significant chronic health conditions that may involve multisystem disease (congenital or acquired), high medical fragility, functional and psychosocial impairment, technology dependence (tracheostomies, MV, feeding tubes) and high resource utilization (frequent and/or prolonged hospitalizations). [19][20][21] Advances in obstetric care, neonatal intensive care, pediatric critical care, and medical technology have resulted in a growing population of CMC dependent on long-term MV.…”
Section: Introductionmentioning
confidence: 99%